Recent advances on the transition-metal-catalyzed synthesis of imidazopyridines: an updated coverage - Reen, Gagandeep Kour; Kumar, Ashok; Sharma, Pratibha (Beilstein Journal of Organic Chemistry, 2019)
A comprehensive account of recent advances in the synthesis of imidazopyridines, assisted through transition-metal-catalyzed multicomponent reactions, C–H activation/functionalization and coupling reactions are highlighted in this review article. The basic illustration of this review comprises of schemes with concise account of explanatory text. The schemes depict the reaction conditions along with a quick look into the mechanism involved to render a deep understanding of the catalytic role. At some instances optimizations of certain features have been illustrated through tables, i.e., selectivity of catalyst, loading of the catalyst and percentage yield with different substrates. Each of the reported examples has been rigorously analyzed for reacting substrates, reaction conditions and transition metals used as the catalyst. This review will be helpful to the chemists in understanding the challenges associated with the reported methods as well as the future possibilities, both in the choice of substrates and catalysts. This review would be quite appealing to a wider range of organic chemists in academia and industrial R&D sectors working in the field of heterocyclic syntheses. In a nutshell, this review will be a guiding torch to envisage: (i) the role of various transition metals in the domain dedicated towards method development and (ii) for the modifications needed thereof in the R&D sector.
Keywords: C–H activation/functionalization; coupling reactions; imidazopyridines; multicomponent reactions; transition metal catalysis